IMPLEMENTASI PEMBELAJARAN DARING PENDIDIKAN AGAMA ISLAM TERHADAP HASIL BELAJAR SISWA DI SMP WAHID HASYIM MALANG - Ainur Rahman; Abdul Jalil; Eko Setiawan (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Online learning is one of the lessons applied at Wahid Hasyim Middle School. Schools conduct online learning because of government policies. Some schools have implemented an online learning system. Thus the researcher wants to raise a title